Implantation Corridors in Canine Thoracic Vertebrae: A Morphometric Study in Dogs of Varying Sizes - Sabol, Julianna C.; Mariani, Christopher L. (Veterinary and Comparative Orthopaedics and Traumatology, 2024)
Objective Surgical stabilization to treat fractures, luxations, and congenital malformations in the thoracic spine can be difficult due to its unique anatomy and surrounding structures. Our objective was to document the morphometrics of the thoracic vertebrae relating to an ideal trajectory for dorsolateral implant placement in a variety of dog sizes and to assess proximity to important adjacent critical anatomical structures using computed tomography (CT) studies.Study Design Medical records for 30 dogs with thoracic CT were evaluated. Implantation corridor parameters for thoracic vertebrae (T1–T13) were measured, including the length, width, angle from midline, and allowable deviation angle for corridors simulated using an ideal implant trajectory. The distances from each vertebra to the trachea, lungs, aorta, subclavian artery, and azygos vein were also measured.Results Implantation corridor widths were often very narrow, particularly in the mid-thoracic region, and allowable deviation angles were frequently small. Distances to critical anatomical structures were often less than 1 mm, even in larger dogs.Conclusion Thoracic implantation requires substantial precision to avoid breaching the canal, ineffective implant placement, and potential life-threatening complications resulting from invasion of surrounding anatomical structures.
Keywords: spinal stabilization; spinal fracture; spinal subluxation; spinal malformation; computed tomography